Molière’s The Miser in Zajec’s post-dramatic adaptation - Vidović, Anđela (Molière u hrvatskoj kulturi, 2024)
The paper analyses the stylistic-semantic shifts within the reading and setting of Molière’s The Miser premiered in January 2021 at the Kerempuh Theatre, directed by Dora Ruždjak Podolski and adapted by Tomislav Zajec. At the same time, Molière’s presence in the Croatian theatre during the last decade, which is less and less immune to the freer correspondences of the template, is being re-examined. Zajec’s reading, marked by the pandemic circumstances of the narrowed auditorium, adds hits, political quotes, phrases from literary and dramatic life, humorous quips to the existing plot in several registers, but also ironizes happy endings. At the same time, the most noticeable change is of a conceptual nature (Anselme becomes Molière himself), which reduces the care of the family nest to intra-theatre referentiality. This opens space for rearrangement of creative autonomy that will keep the skeleton, but still completely escape the original.